Comparative field studies of biochemical and agro-physiological parameters in semi-arid zone with rainfall Moroccan climate of durum wheat - Saghouri El Idrissi Imane; Kettani Rajae; Ferrahi Moha; El Fechtali Mohamed; Ziri Rabea; Brhadda Najiba (Journal of Agriculture and Food Research, 2023)
Durum wheat production is highly unpredictable throughout the year because of uncertain rainfall and frequent dry spells and it is absolutely necessary to characterize the impact of drought on grain yield. The objective in this research is to carry out a comparative analysis of biochemical and physiological responses and production parameters of durum wheat (Triticum durum) in semi-arid zone with rainfall in Morocco's climates. Thirteen durum wheat genotypes selected at INRA-Morocco and three control varieties were evaluated under Moroccan rainfed conditions for two growing seasons (2019/20 and 2020/21). The INRA-Morocco-Douyet Fez experimental field site was where the trials were conducted (34°2 N, 5°W, 416 m). Different parameters were studied. Five physiological, four agronomical and one biochemical trait are measured in this study: leaf area, leaf temperature, relative water content, chlorophyll content, proline, yield and yield components. Decreased rainfall significantly increased proline content, leaf temperature and decreased leaf area, grain yield, chlorophyll and relative water content (P < 0.01). Based on these results, field-induced rainfall variations resulted in inconsistencies in the response of the assessed traits to drought-related interactions between both growing seasons (2020–2021) in order to identify stable, high-yielding genotypes in the presence and absence of rainfall, which requires a strong association of drought-related traits.